Meningkatkan Hasil Belajar Ips Menggunakan Media Pop-Up Pada Siswa SD - Saleh, Sufri (Peneliti.net, 2024)
This study aims to determine the improvement of learning outcomes of Social Sciences (IPS) of fifth grade students of SD Negeri 29 Kota Ternate using pop-up media. This type of research is Classroom Action Research (CAR). The subjects of this study were fifth grade students of SD Negeri 29 Kota Ternate with a total of 21 students. The research model used is the Kemmis and Mc. Taggart model, which consists of the planning stage, the action and observation stage, and the reflection stage. Data collection techniques using tests. The data analysis techniques used are quantitative analysis and qualitative analysis. To ensure the validity of the data, the source triangulation technique is used. In IPS learning activities using pop-up media, the teacher divides students into three groups, where each group gets a different pop-up book. Each student gets a student worksheet that matches the material on the pop-up media. Then, group representatives present the results of their group discussions in front of the class. Using pop-up media can improve students' IPS learning outcomes. This is evidenced by the increase in student learning outcomes in social studies, namely in the initial pre-action conditions the average class learning outcomes were 64.28 with a completion percentage of 42.86%. After the action was carried out in cycle I, the average class learning outcomes were 73.46 with a completion percentage of 71% and after the action was carried out in cycle II, the average class learning outcomes were 80.47 with a passing percentage of 80.95%. This means that the research target to improve student learning completion is in accordance with the research success indicators, namely 75% of students who take part in social studies learning using pop-up media get a score of ≥ 70.